2023
DOI: 10.3390/cancers15153836
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Bioenergetics and Tumor Microenvironments—Enhancing Chemotherapeutics and Targeting Resistant Niches through Nanosystems

Abstract: Cancer is an impending bottleneck in the advanced scientific workflow to achieve diagnostic, prognostic, and therapeutic success. Most cancers are refractory to conventional diagnostic and chemotherapeutics due to their limited targetability, specificity, solubility, and side effects. The inherent ability of each cancer to evolve through various genetic and epigenetic transformations and metabolic reprogramming underlies therapeutic limitations. Though tumor microenvironments (TMEs) are quite well understood i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 289 publications
0
2
0
Order By: Relevance
“…The end-product of the glutaminolysis pathway is succinate (see Figure 4), which also contributes to extracellular acidification [185,186]. Furthermore, hyperosmolarity contributes to pH acidification by increasing extracellular Na+ concentration levels, which promotes aerobic glycolysis and leads to lactate accumulation [180,187,188]. Lactagenesis is a highly orchestrated effort that contributes to glycolysis, glutaminolysis, lactate production, a decrease of mitochondrial functions, angiogenesis, immunosuppression, cell migration, and metastases [185,189,190].…”
Section: Phmentioning
confidence: 99%
“…The end-product of the glutaminolysis pathway is succinate (see Figure 4), which also contributes to extracellular acidification [185,186]. Furthermore, hyperosmolarity contributes to pH acidification by increasing extracellular Na+ concentration levels, which promotes aerobic glycolysis and leads to lactate accumulation [180,187,188]. Lactagenesis is a highly orchestrated effort that contributes to glycolysis, glutaminolysis, lactate production, a decrease of mitochondrial functions, angiogenesis, immunosuppression, cell migration, and metastases [185,189,190].…”
Section: Phmentioning
confidence: 99%
“…[9][10][11][12] Recent literature has demonstrated that mitochondria remain functional even in cases where aerobic glycolysis is occurring as a means to offer biosynthetic intermediates to anabolic-proliferating cells while serving as sources of bioenergetics to cells in oxygenated environments. [13][14][15] Thus, targeting both glycolysis and mitochondrial respiration may provide a more durable treatment strategy when compared to targeting a single pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GNP can be utilized in photothermal therapy, where they convert absorbed light energy into heat, selectively ablating cancer cells while sparing healthy tissue [43,44]. With ongoing research and advancements, gold nanoparticles hold great potential as therapeutics and imaging agents in a wide range of medical applications, offering opportunities for personalized and precise treatments in the future [45,46]. In this study, we proposed, for the first time, that GNP have the ability to suppress the over-secretion of IL-6 through modulation mediated by miRNAs.…”
Section: Introductionmentioning
confidence: 99%